Colletotrichum xishanense as a new etiological anthracnose agent on Fagopyrum gracilipes in Yunnan Province, China - Zhao, Shi-Yi; Wang, Qiu-Tong; Guo, Mei-Jun; Hou, Cheng-Lin (Phytotaxa, 2024)
Buckwheat (Fagopyrum spp.) is an important agricultural crop in some remote regions of China. In this study, two strains of Colletotrichum were isolated from brown and grey-white spots on the leaves of Fagopyrum gracilipes in Yunnan Province, China. Phylogenetic analyses inferred from combined ITS, act, chs-1, cal, gapdh, apmat, gs, and tub2 sequences revealed that these isolates are a new species, belonging to the C. gloeosporioides species complex and therefore we introduce as Colletotrichum xishanense. Pathogenicity tests indicated that C. xishanense infects not only herbaceous plant but also woody plant. Given the broader host range and stronger pathogenicity, it is time to focus on disease management and resistance breeding.